Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1242/dev.111740
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1 controls the morphogenesis of pharyngeal pouch epithelia through mesodermal Wnt11r and Fgf8a

Abstract: The pharyngeal pouches are a segmental series of epithelial structures that organize the embryonic vertebrate face. In mice and zebrafish that carry mutations in homologs of the DiGeorge syndrome gene TBX1, a lack of pouches correlates with severe craniofacial defects, yet how Tbx1 controls pouch development remains unclear. Using mutant and transgenic rescue experiments in zebrafish, we show that Tbx1 functions in the mesoderm to promote the morphogenesis of pouch-forming endoderm through wnt11r and fgf8a exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 54 publications
6
66
0
Order By: Relevance
“…Additionally, we showed that endodermal pax1 plays an indispensable role in segmental pouch formation, except for the first pouch and anterior wall of the second pouch. Importantly, pax1 is required for the endodermal activation of tbx1 and fgf3 transcription, the functions of which in the development and patterning of endodermal pouches were described previously (Piotrowski et al, 2003;Crump et al, 2004;Herzog et al, 2004;Choe and Crump, 2014). The results of our TUNEL assay did not suggest an increase in apoptosis in the pharyngeal endoderm of the pax1 mutants.…”
Section: Impact Of Pax1 On Pharyngeal Segmentation and Derivativessupporting
confidence: 64%
See 4 more Smart Citations
“…Additionally, we showed that endodermal pax1 plays an indispensable role in segmental pouch formation, except for the first pouch and anterior wall of the second pouch. Importantly, pax1 is required for the endodermal activation of tbx1 and fgf3 transcription, the functions of which in the development and patterning of endodermal pouches were described previously (Piotrowski et al, 2003;Crump et al, 2004;Herzog et al, 2004;Choe and Crump, 2014). The results of our TUNEL assay did not suggest an increase in apoptosis in the pharyngeal endoderm of the pax1 mutants.…”
Section: Impact Of Pax1 On Pharyngeal Segmentation and Derivativessupporting
confidence: 64%
“…In zebrafish, the expression of fgf3 in the pharyngeal endoderm of tbx1 mutants is not affected, although they lack pouch segmentation (Choe and Crump, 2014). At stage 23 in the wild type, expression of fgf3 was detected in endodermal cells of the first, second and third pouches as well as in the midbrain-hindbrain boundary, and fgf3 expression in the first and third pouches was much weaker than in the second pouch (Fig.…”
Section: Reiterative Development Of the Third And Posterior Pouches Rmentioning
confidence: 93%
See 3 more Smart Citations